The Effectiveness of a Virtual Reality-Based Exergame Protocol in Improving Postural Balance in Older Adults During the COVID-19 Pandemic - Valeska Gatica-Rojas; María Isabel Camoglino-Escobar; Hernán Carrillo-Bestagno; Ricardo Cartes-Velásquez (Multimodal Technologies and Interaction)
Background: The COVID-19 pandemic significantly reduced physical activity levels, particularly among older people, negatively impacting their postural balance and increasing the risk of falls and hip fractures. This study aims to assess the effect of a virtual reality-based exergame physical activity protocol at home on improving postural balance in older people. Materials and Methods: A quasi-experimental design was employed with 10 older people (71 ± 9 years) who participated in a virtual reality-based exergame physical activity protocol consisting of eighteen 25 min sessions conducted at home. The protocol incorporated 3D movement tracking using a sensor attached to the participants’ bodies to monitor postural sway in real time. Clinical measurements included the Timed Up and Go test and posturographic measures of center-of-pressure, including sway area, velocity, and standard deviation in the mediolateral and anteroposterior directions under four conditions: static with the eyes open and eyes closed and dynamic voluntary sway in the mediolateral direction following a 30 Hz metronome with the eyes open and eyes closed. Paired t-tests were used to compare pre- and post-intervention data. Results: The intervention led to significant improvements in postural balance as measured using both posturographic measures (p < 0.05) and the Timed Up and Go test (p = 0.04). Conclusion: The virtual reality-based exergame physical activity protocol conducted at home, comprising eighteen 25 min sessions, effectively improves postural balance in older people.